Universal entire functions with additional properties - M. Niess (Հայաստանի ԳԱԱ)
The aim of this note is the construction of universal entire functions of a new type. In particular, these functions are universal under translations and are bounded on each line and have zeros at certain prescribed points.
Keywords: Mathematics; Science